On additivity of derivations - Sandhu, G.S.; Kumar, D. (Carpathian Mathematical Publications, 2019)
Let R be a ring and M be an R-bimodule. A mapping d:R→ M (not necessarily additive) is called multiplicative derivation of R if d(xy)=d(x)y+xd(y) for all x,yR. In this paper, we intend to establish the additivity of d under some suitable restrictions. Moreover, we introduce multiplicative semi-derivations of rings and discuss their additivity.